2008
DOI: 10.1002/jcp.21530
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Kv2.1‐FAK complex as a mechanism of FAK activation, cell polarization and enhanced motility

Abstract: Focal adhesion kinase (FAK) plays key roles in cell adhesion and migration. We now report that the delayed rectifier Kv2.1 potassium channel, through its LD-like motif in N-terminus, may interact with FAK and enhance phosphorylation of FAK397 and FAK576/577. Overlapping distribution of Kv2.1 and FAK was observed on soma and proximal dendrites of cortical neurons. FAK expression promotes a polarized membrane distribution of the Kv2.1 channel. In Kv2.1-transfected CHO cells, formation of the Kv2.1-FAK complex wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 58 publications
3
53
0
Order By: Relevance
“…Consistently, K ϩ channel blockers such as tetraethylammonium (TEA) and 4-aminopyridine inhibit cell migration (17,39,42,49). Our investigation has shown that the Kv2.1 K ϩ channel can act as an "adhesion protein," form a complex with FAK, and promote the activation of FAK in both neuronal and nonneuronal cells (51). The interaction of Kv2.1 with FAK enhances FAK 576/577 and FAK 397 phosphorylation, significantly increases cell adhesion and directional migration in wound healing processes both in vitro and in animal models (51).…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…Consistently, K ϩ channel blockers such as tetraethylammonium (TEA) and 4-aminopyridine inhibit cell migration (17,39,42,49). Our investigation has shown that the Kv2.1 K ϩ channel can act as an "adhesion protein," form a complex with FAK, and promote the activation of FAK in both neuronal and nonneuronal cells (51). The interaction of Kv2.1 with FAK enhances FAK 576/577 and FAK 397 phosphorylation, significantly increases cell adhesion and directional migration in wound healing processes both in vitro and in animal models (51).…”
mentioning
confidence: 70%
“…Our investigation has shown that the Kv2.1 K ϩ channel can act as an "adhesion protein," form a complex with FAK, and promote the activation of FAK in both neuronal and nonneuronal cells (51). The interaction of Kv2.1 with FAK enhances FAK 576/577 and FAK 397 phosphorylation, significantly increases cell adhesion and directional migration in wound healing processes both in vitro and in animal models (51). Taken together, these data suggest that the Kv2.1 protein is a potent promoter for cell migration via increasing activation of FAK.…”
mentioning
confidence: 88%
See 3 more Smart Citations